Influence of Political and Socioeconomic Factors on Population Distribution in Bosnia and Herzegovina - Nezirović, Senada (Journal for Geography, 2023)
The findings suggest that the political situation in Bosnia and Herzegovina significantly impacts population distribution across the entire territory. It can be concluded that the deterioration of specific socioeconomic conditions (e.g., employment, living standards) in the country is reflected in the overall demographic trends. The paper provides an overview of the political processes before and after the conflict in Bosnia and Herzegovina, which have led to an imbalanced and potentially problematic distribution of population throughout the territory. Additionally, it discusses the detailed socioeconomic conditions in past decades, which have contributed to continuous migration from Bosnia and Herzegovina to European Union countries. Demographic analyses drew upon the results of the last two censuses conducted in 1991 and 2013, documenting the latest distribution of population and density changes.